EFEKTIVITAS PENYULUHAN PERTANIAN KOMODITI BAWANG MERAH PADA KELOMPOK TANI BAROKAH JAYA DESA BEJI, KECAMATAN JUNREJO, KOTA BATU - Jemadu, Maria Angelina Yunita; Arvianti, Eri Yusnita; Kholil, A. Yusuf (Universitas Tribhuwana Tunggadewi, 2024)
This research aimed to determine the effectiveness of agricultural extension for the shallot commodity in the Barokah Jaya farmer group in Beji Village, Junrejo District, Batu City. This research used a scoring system or score scale and administration technique. Training, guidance, and evaluation are the success metrics used in this research. The results show that the shallot farming extension activities of the Barokah Jaya Farmers Group can be assessed as effective by percentage. According to the operation of implementing extension training, which has a success rate of 79%, they are considered very successful. Implementing the support provided to farmers by extension workers was considered successful with a percentage of 70.5%. Implement training provided to farmers by extension workers, with a proportion of 63.5%. The evaluation procedure was assessed as successful in 69% of cases. This makes it possible to guarantee the success and satisfaction of shallot farming extension efforts in Beji Village.